Importance of the review on floristic and phytosociological studies of the arboreal stratum of the seasonal deciduous forest of the Serra Geral slope, Rio Grande do Sul, Brazil, to support proposals for sustainable management - Zerwes, Cristian Mateus (2018)
The Seasonal Deciduous Forest (FED) is a deciduous and human-caused impacted vegetation, occurring at the Upper Rio Uruguay basin and at the southern slope of Serra Geral plateau, Rio Grande do Sul state. The aim of this study is to compile results of tree layer floristics and phytosociological surveys on FED of Serra Geral escarpment with the intention of supporting future interventions for the recovery of degraded areas and sustainable management projects. To obtain the data, was held a narrative review from 62 selected works from the digital libraries of CAPES, Scielo and Google Scholar. For quantitative variables, was calculated the median, standard deviation and amplitude. The hodgepodge of methods used in the surveys conducts to difficulties in comparing data. The median species richness is 54 and the Shannon-Wiener diversity index median is 3.10 nats. The analyzed surveys show very important information to define methods and planning for conservation, degraded area recovery and sustainable use of forest resources.